"Changing Ground." Travel writing about Iceland over a fifty year interval - Rósa María Sigurðardóttir 1966- (2011)
This essay examines the relations between two travel books about Iceland, Letters from Iceland by W. H. Auden and Louis MacNeice that was published in 1937 and Moon Country: Further Reports from Iceland by Simon Armitage and Glyn Maxwell published in 1996. It observes the characteristics of each book, points out their similarities and compares them briefly with other travel writings on Iceland. Both books are compiled of several different types of material; poetry, letters and various other things. The construction of the two books is distinctly different from most other travel writings about Iceland. They are far from being entirely identical in construction but are still more akin than can be ignored. The fact that their authors are all poets may have its influence on the outcome. Breaking up the more conventional form of travel stories gives the works a somewhat light hearted air, although not frivolous. The writers avoid any kind of too linear a narrative and manage to put their own special signature on the travel writing genre. The results are two books that bring refreshing breaths of air into a well established genre, demonstrating its flexibility and showing its possibilities and diversity.